δ-Almost Ricci soliton on 3-dimensional trans-Sasakian manifold - Acet, T. (Carpathian Mathematical Publications, 2024)
In this paper, we consider δ-almost Ricci soliton on 3-dimensional trans-Sasakian manifold admitting η-parallel Ricci tensor. We give some conditions for P· φ =0, P· S=0, Q· P=0. Also, we show that there is almost pseudo symmetric δ-almost Ricci soliton on 3-dimensional trans-Sasakian manifold admitting cyclic Ricci tensor. Finally, we give an example for verifying the obtained results.